Presepsin and Mortality Risk in Sepsis: A Valuable Tool for Predicting Patient Survival - Agustin Iskandar; Yeni Ayu Prihastuti; Indah Adhita Wulanda; Andrea Aprilia; Muhammad Anshory (Trends in Immunotherapy, 2025)
Background: Early identification of high-risk sepsis patients is essential for timely intervention and improved survival. Prognostic biomarkers can support clinical decision-making by stratifying mortality risk and informing treatment choices. Sepsis remains a major global health challenge due to its complex management and high mortality rate. Presepsin, a soluble CD14 subtype (sCD14-ST), has emerged as a promising biomarker for sepsis prognosis, demonstrating superior predictive value compared to conventional markers like procalcitonin (PCT). This study aims to evaluate the prognostic significance of Presepsin in predicting mortality among sepsis patients. Methods: A prospective cohort study was conducted on 110 adult sepsis patients admitted to the ICU at Dr. Saiful Anwar Hospital, Malang, from November 2018 to October 2019. Patients were diagnosed using the Sepsis-3 criteria, and Presepsin levels were measured using the chemiluminescent immunoassay (CLIA) method. Survival analysis was performed using Kaplan-Meier curves, and hazard ratios (HR) were calculated through Cox regression. Results: The ROC analysis identified 17,085 pg/mL as the optimal Presepsin threshold for predicting mortality (AUC: 0.939, 95% CI: 0.897–0.982, p < 0.001). Patients with Presepsin levels ≥17,085 pg/mL had a significantly lower median survival (3 days) compared to those with lower levels (9 days) (HR 3.654, 95% CI: 1.978–6.752, p < 0.001). Among patients with high Presepsin levels, 32 of 33 (96.9%) died, whereas only 28 of 77 (36.4%) patients with lower levels experienced mortality. Conclusion: Presepsin shows potential as a biomarker for identifying sepsis patients at increased risk of mortality. Its use may support early risk stratification and guide clinical decision-making in sepsis management.